(2x+1)+(3x+10)+68=180

Simple and best practice solution for (2x+1)+(3x+10)+68=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+1)+(3x+10)+68=180 equation:


Simplifying
(2x + 1) + (3x + 10) + 68 = 180

Reorder the terms:
(1 + 2x) + (3x + 10) + 68 = 180

Remove parenthesis around (1 + 2x)
1 + 2x + (3x + 10) + 68 = 180

Reorder the terms:
1 + 2x + (10 + 3x) + 68 = 180

Remove parenthesis around (10 + 3x)
1 + 2x + 10 + 3x + 68 = 180

Reorder the terms:
1 + 10 + 68 + 2x + 3x = 180

Combine like terms: 1 + 10 = 11
11 + 68 + 2x + 3x = 180

Combine like terms: 11 + 68 = 79
79 + 2x + 3x = 180

Combine like terms: 2x + 3x = 5x
79 + 5x = 180

Solving
79 + 5x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-79' to each side of the equation.
79 + -79 + 5x = 180 + -79

Combine like terms: 79 + -79 = 0
0 + 5x = 180 + -79
5x = 180 + -79

Combine like terms: 180 + -79 = 101
5x = 101

Divide each side by '5'.
x = 20.2

Simplifying
x = 20.2

See similar equations:

| 2+8.3x=4.6+4.2x | | 7j+2=3 | | -6-9+17q=19q+11 | | 5.77x+1=33.2929+x | | S=54-.08(54) | | F(u)=u^3-10 | | .4x=-.8+2 | | 3-9k-19=-7-10k | | 15+u-22=9(2) | | 6x+35=59 | | -4s--8=142 | | 9x-7-2x=56 | | -4t-15+8t=2t+19 | | 3x+7+2x-1=11 | | 7.8+6=23.16 | | 7.8+6=23.16 | | 126+22+4x=180 | | 6x-15=x+5(3+x) | | (x+3)(x+3)=8x | | 20-16y=-19-19y | | p+4b=120 | | 2x+x+(x+2)=30 | | -208=-21x+212 | | -11-22=33 | | 7(4x-5)-4(6x-5)=-91 | | -2j-20=8j | | 8z=122 | | 65+90+5x=180 | | -3-y-X=0 | | 2x-8=-8x-24 | | 2(4-9w)= | | 57+51+9x=180 |

Equations solver categories